Desegregating the dollar : African American consumerism in the twentieth century - Weems, Robert E., 1951- (Book collections on Project MUSE., 1998)
Despite African Americans' nearly $500 billion collective annual spending power, surprisingly little attention has been devoted to the ways U.S. businesses have courted black dollars in postslavery America. Desegregating the Dollar presents the first fully integrated history of black consumerism during the last century.